Isolation and Characterization of Serum Extracellular Vesicles (EVs) from Atlantic Salmon Infected with Piscirickettsia Salmonis - Leidy Lagos; Julia Tandberg; Alexander Kashulin-Bekkelund; Duncan Colquhoun; Henning Sørum; Hanne Winther-Larsen (Proteomes, 2017)
Secretion of extracellular vesicles (EVs) is a common feature of both eukaryotic and prokaryotic cells. Isolated EVs have been shown to contain different types of molecules, including proteins and nucleic acids, and are reported to be key players in intercellular communication. Little is known, however, of EV secretion in fish, or the effect of infection on EV release and content. In the present study, EVs were isolated from the serum of healthy and Piscirickettsia salmonis infected Atlantic salmon in order to evaluate the effect of infection on EV secretion. P. salmonis is facultative intracellular bacterium that causes a systemic infection disease in farmed salmonids. EVs isolated from both infected and non-infected fish had an average diameter of 230–300 nm, as confirmed by transmission electron microscopy, nanoparticle tracking, and flow cytometry. Mass spectrometry identified 180 proteins in serum EVs from both groups of fish. Interestingly, 35 unique proteins were identified in serum EVs isolated from the fish infected with P. salmonis. These unique proteins included proteasomes subunits, granulins, and major histocompatibility class I and II. Our results suggest that EV release could be part of a mechanism in which host stimulatory molecules are released from infected cells to promote an immune response.